2020
DOI: 10.5194/bg-2020-140
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Technical note: Estimating light-use efficiency of benthic habitats using underwater O<sub>2</sub> eddy covariance

Abstract: Light-use efficiency defines the ability of primary producers to convert sunlight energy to primary 10 production and is computed as the ratio between the gross primary production and the intercepted photosynthetic active radiation. While this measure has been applied broadly within the atmospheric sciences to investigate resource-use efficiency in terrestrial habitats, it remains underused within the aquatic realm. This report provides a conceptual framework to compute hourly and daily light-use efficiency us… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…The modeled flux was able to better predict the smaller measured fluxes in the afternoon at the same light levels compared to the observed morning measurements. Our findings provide the first evidence, based on extensive metabolic aquatic eddy covariance measurements under naturally varying conditions, for substantial variation in seagrass respiration which is likely due to the production and consumption of highly labile compounds over the diel cycle; a dynamic mechanism that has been hypothesized in previous studies (Howarth et al 2014;Rheuban et al 2014b;Attard and Glud 2020). Fig.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The modeled flux was able to better predict the smaller measured fluxes in the afternoon at the same light levels compared to the observed morning measurements. Our findings provide the first evidence, based on extensive metabolic aquatic eddy covariance measurements under naturally varying conditions, for substantial variation in seagrass respiration which is likely due to the production and consumption of highly labile compounds over the diel cycle; a dynamic mechanism that has been hypothesized in previous studies (Howarth et al 2014;Rheuban et al 2014b;Attard and Glud 2020). Fig.…”
Section: Discussionsupporting
confidence: 65%
“…Several studies found that O 2 fluxes in seagrass meadows show a higher net release of O 2 in the morning than in the afternoon at the same light levels (Hanelt 1992;Rheuban et al 2014b;Berg et al 2017Berg et al , 2019Koopmans et al 2020). Multiple explanations for this have been proposed, including afternoon depletion in water column CO 2 limiting photosynthetic production (Berg et al 2019), increased afternoon water temperature (Masini and Manning 1997;Rheuban et al 2014a), photoinhibition (Hanelt 1992), and enhanced consumption of highly labile organic compounds produced during photosynthesis causing respiration to vary over the course of a day (Glud 2008;Howarth et al 2014;Rheuban et al 2014b;Attard and Glud 2020). It is commonly assumed that respiration stays constant throughout the day and night in calculations of daily GPP and R (Hume et al 2011;Koopmans et al 2020;Rheuban et al 2014a).…”
mentioning
confidence: 99%
“…Both measurements can reveal environmental and physiological limitations of photosynthesis. Falkowski and Raven (1997) provide a useful summary in Chapter 3.…”
Section: Introductionmentioning
confidence: 99%